2022
DOI: 10.3389/fenvs.2022.1043434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of agricultural subsidies on heterogeneous farmers’ fertilizer application intensity and its mediating mechanism: Based on China household finance survey database

Abstract: Agricultural subsidies have an important effect on the farmer’s fertilizer application behavior, but the differences in the effect on different farmers and its mediating mechanism have not been sufficiently studied. Using relevant data from the CFHS database in 2015, this paper focused on the differences in the effect of agricultural subsidies on fertilizer application intensity among farmers with different operation scales and planting structures, as well as the mediating mechanism of the effect of agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…GASP allocates 20% of subsidy funds to encouraging farmers to adopt green, low-carbon practices. Farmers who receive subsidies have more funds available to adopt conservation farming patterns, such as replacing chemical fertilizers with organic fertilizers and adopting agro-film recycling projects (He et al, 2022) [29]. Third, GASP reduces ACEs by improving the environmental awareness of farmers.…”
Section: Gasp and Aces' Reductionmentioning
confidence: 99%
“…GASP allocates 20% of subsidy funds to encouraging farmers to adopt green, low-carbon practices. Farmers who receive subsidies have more funds available to adopt conservation farming patterns, such as replacing chemical fertilizers with organic fertilizers and adopting agro-film recycling projects (He et al, 2022) [29]. Third, GASP reduces ACEs by improving the environmental awareness of farmers.…”
Section: Gasp and Aces' Reductionmentioning
confidence: 99%
“…As we all know, agricultural subsidies can cover part of the expense of rural households in major producing areas. The increase in the budget for fertilizer and pesticides will result in changes in households’ usage patterns [ 21 , 42 , 78 , 79 ]. Without subsidies, the rural households that produce grain have to pay for the expense of fertilizer and pesticides.…”
Section: Theoretical Analysis and Research Hypothesesmentioning
confidence: 99%
“…Regarding fertilizer application, Kugbadzor [ 39 ] evaluated the influence of the Fertilizer Subsidy Program (FSP) on agricultural output in Ghana. The results indicated that the national output elasticity increased when the FSP was implemented [ 42 ]. The study indicated that agricultural subsidies helped rural households minimize their use of fertilizer [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the other strand of the literature held the opposite point of view. He et al (2022) found that believed that agricultural subsidies for improved crop strains and seeds, the direct subsidy for grain growers, and the comprehensive subsidy for agricultural material increased farmers' fertilizer application. The third group analyzes the impacts of agricultural subsidies on the usage of fertilizer in terms of theory.…”
Section: Introductionmentioning
confidence: 99%